The Role of Children in Supporting Parents to Perform Hajj amongst the Muslim Family: (Sokongan Kewangan Anak Lelaki dan Perempuan dalam Membantu Ibu Bapa Mengerjakan Haji) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
Performing the hajj is the dream of every Muslim. Among the factors that parents consider when achieving this dream include dependent children and insufficient money. Therefore, the most suitable time for them to perform this long-held dream is when their children are grown up and working. This study aims to survey the extent of financial assistance from children that can help parents to perform the hajj. Furthermore, this study will compare the financial efforts of children towards their parents based on gender. The respondents for this study comprised 10 mothers and fathers aged 60 to 80 years who are of Malay ethnicity and of the Islamic faith. Respondents were selected using the purposive sampling technique, and they were interviewed in depth. The data and information resulting from the in-depth interviews were analysed using content analysis and arranged according to themes after they were transcribed and discussed. The results showed that support in the form of random cash contributions and full financing have successfully realized a few of the parents' lifetime dream of performing the hajj. This study has contributed knowledge regarding the role of monetary support from sons and daughters to help their parents fulfil their ambition to perform the hajj, which is a mass pilgrimage that is obligatory to all Muslims, especially for the elderly who wish to achieve their dream of fulfilling the fifth pillar of Islam.Keywords: parents, monetary help, sons, daughters, the hajj, the fifth pillar of Islam